Clinical Reasoning: Development of a Grading Rubric for Student Assessment. Issue 3 (2015) - Furze, Jennifer; Gale, Judith R.; Black, Lisa; Cochran, Teresa M.; Jensen, Gail M.
Abstract : Background and Purpose. : Clinical reasoning is a complex but vital skill required for professional physical therapy practice. Experts agree that clinical reasoning is both difficult to define and challenging to assess. In order to facilitate the development of clinical reasoning skills in physical therapist (PT) students, educators need to be able to evaluate this process. The purpose of this paper is to describe the development and revision of a tool to assess PT student clinical reasoning skills across the curriculum. Method/Model Description and Evaluation. : A Clinical Reasoning Grading Rubric was created using the following multistep process: (1) Initial pilot research exploring the clinical reasoning process students used in a performance‐based examination, (2) use of theoretical constructs from cognitive learning theory and learner skill acquisition, (3) content expert review, and (4) feedback from key stakeholder groups (clinicians, faculty, and students). Outcomes. : The rubric was developed to assess student clinical reasoning skills across the curriculum and evaluate student readiness for the clinical setting. The tool allows faculty and students a structure to identify and track the progression of student reasoning skill development. Discussion and Conclusion. : The Clinical Reasoning Grading Rubric is 1 tool that can be used to evaluate the clinical reasoning of students at multiple points in time across the curriculum. This instrument has applicability for assessment of clinical reasoning skill development from clinical to residency education. The rubric also provides insight into the teaching and learning environment and may be helpful in informing pedagogical strategies and curriculum change.